The IMPACT OF SOCIOECONOMIC STATUS AND DEMOGRAPHIC ON SUBJECTIVE WELL-BEING IN INDONESIA 2014-2015: A CROSS-SECTIONAL STUDY - Maria Veronika Simanjuntak; Tri Damayanti Simanjuntak (Universitas Djuanda Bogor, 2023)
Subjective well-being is described as a person’s level of happiness and satisfaction with their life. Subjective well-being is critical in developing and sustaining a healthy and productive society. The negative consequence of not achieving subjective well-being is the formation of bad sentiments, emotions, or moods, which can harm health and raise the risk of disease. Several early studies were confined to certain groups, and this subjective will-being research across Indonesia utilizing IFLS secondary data is still limited. This research aims to examine the impact of socioeconomic status and demographic characteristics on subjective well-being in the Indonesian population using a cross-sectional study design using secondary data from the Indonesia Family Life Survey (IFLS5) wave 5, 2014-2015, the inclusion and exclusion criteria were met by a total of 30,147 respondents. This study will employ stratified random sampling, which is consistent with that used in IFLS5, and the data acquired will be examined through univariate, bivariate, and multivariate analysis. As many as 13.69% of respondents were unsatisfied with their lives in general. After controlling job satisfaction, job stress, economic level, age, and gender, the greatest variable on subjective well-being is job satisfaction, which is equal to 5.38 times (95% CI 4.94 - 5.987; p-value 0.001). This means that respondents who are dissatisfied with their work are also at risk of feeling dissatisfied with subjective well-being.